A study on the social acceptability of the biodegradable waste management program of the municipality of Teresa in the province of Rizal - Silva, Liz C. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Biodegradable wastes have the largest waste composition among solid wastes estimated at about 50 percent. This necessitates closer attention in solid waste management (SWM) because of their contribution in climate change. However, few studies focus on the social dimensions of biodegradable wastes management (BWM) specifically the behavior of waste generators. Thus, there is a need to study the behavior of waste generators to develop implementation mechanisms for WM program at the local level based on social acceptability. The Theory of Planned Behavior (TPB) presents a framework that reveals the behavoir of individuals towards SWM, particularly the participation of waste generators in the SWM programs. TPB provides the factors, through its constructs, which determine the social acceptability of the BWN. In the study, a baseline analysis was conducted which supported that there are massive information, education and communication (IEC) campaigns and presence of support facilities to facilitate BWM in the community. A household survey was conducted to determine the perception of the respondents on BWM. The survey results were subjected to correlation analysis before proceeding with the path analysis. The study revealed that the knowledge imparted through massive IEC, together with social pressure and operational support facilities, made it possible for the community to socially accept BWM, as shown in the results of the correlation analysis between attitude and perceived behavioral control (r=0.598,p,0.1,2-tailed). Furthermore, the factors of the TPB-attitude, subjective norms, and perceived behavioral control-have statistically significant relationships with each other as well as with social acceptability. Subjective norms (p=0.566,p<0.1,2-tailed) have the greatest influence on the social acceptability of BWM. This indicates the importance of considering social acceptability of BWM in the preparation and implementation of waste management program at the local level.